The lightning flash - Cooray, Vernon (IET power and energy series, 2014)
This book presents the second edition about lightning flash. The second edition is significantly expanded by the addition of nine new chapters on various subjects related to lightning including triggered lightning, high-speed video observations, nitrogen oxide production, energetic radiation emissions, upper atmospheric electrical discharges, lightning attachment and influence of lightning on climate. All but four chapters of the previous edition have been modified to include the latest research work on the subject. I hope that the lightning research community will find this edition of the book to be both educational and instrumental in tackling new challenges in lightning research.